Entering the 5G Era : Lessons from Korea - Hong, Een Kee (World Bank, Washington, DC, 2021)
In April 2019, the Republic of Korea launched the world’s first smart phone based, business-to-consumer (B2C) 5G commercial services. In two years, the country’s 5G subscribers surpassed 13 million, accounting for 20 percent of total mobile subscriptions. Globally, 5G is in the early stage of development both from market and technology perspectives. However, Korea is one of the countries that have demonstrated early successes in bringing a domestic network to scale and building a comprehensive national strategy to maximize the transformative potential of 5G. The country’s experience shows that even in countries with mature mobile industry, the government role is still critical as a key enabler for 5G ecosystem development. The government provided strategic clarity and adopted an inclusive process in the implementation of the new generation mobile network. This case study examines the lessons learned from Korea’s 5G journey, with a focus on the government strategy and actions to nurture the ecosystem development. The challenges and the lessons learned from Korea’s early experience can offer interesting insights to other countries planning to deploy 5G in the coming years.